Security in Optical Communication Systems: Data Encryption and beyond - Abbade, Marcelo Luis Francisco [UNESP]; Junior, Pedro Paulo Pareto; Rodrigues, Ivan Eduardo Lage [UNESP]; Souza, Welerson Santos; Bonani, Luiz Henrique [UNESP]; Aldaya, Ivan [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2021)
Optical communication systems (OCSs) are prone to a myriad of security threats, such as fiber cutting, tapping, and jamming. However, OCSs also provide appropriate conditions for the exchange of encryption keys by quantum-based approaches and for the emergence of signal encryption. Both these strategies may lead to unprecedented levels of security. In this paper, we present a brief review on the security menaces and opportunities related to OCSs. Encryption-based solutions receive special attention.